Application of clean agents in fire suppression systems: an overview - Jum’azulhisham, Abdul Shukor; Muhammad Al-Hapis, Abdul Razak; Azmi, Hassan; Jamian, Rahim (Springer, 2021)
The application of clean agent for fire extinguishing evolves from time to time. Lately, there is an increasing number of applications of F-gaseous in refrigeration, air-conditioning, and blowing agent as well. This includes the use of fluorine gas as its extinguishing agent. The application of clean agents in the fire suppression systems is better than before. These agents are reviewed in this paper together with other gaseous. The awareness of greenhouse effects, climate change, ozone depletion and global warming enables innovative green technologies to grow more rapidly for the sustainability of the future generation. This study aims to choose the needs of the new fire suppression clean agent to comply with the standards and regulations. The study of fluorinated gaseous (F-gaseous) in this paper brings to the needs of a new study of new gaseous focused to counter global warming. The study will also include related computational models and experimental investigations conducted for the research related in the gas type clean agent fire systems to suit to the effectiveness of its application. This article presents a review of these studies, the trend of studies and suggests a direction for future research developments.